2017
DOI: 10.1002/gps.4695
|View full text |Cite
|
Sign up to set email alerts
|

Different apathy clinical profile and neural correlates in behavioral variant frontotemporal dementia and Alzheimer's disease

Abstract: Objectives: Apathy is one of the most common and disabling syndromes of dementia. Clinical apathy expression and neuroanatomical basis of apathy seem to differ between behavioral variant frontotemporal dementia (bvFTD) and Alzheimer's disease (AD), although evidence is scarce and poorly understood. Our main purposes were to compare the clinical apathy profile from patients with bvFTD and AD and analyze the relationship between apathy and brain metabolism measured using positron emission tomography imaging with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 64 publications
2
34
0
Order By: Relevance
“…Additionally, deficits of emotional processing, social awareness [54] and emotional decision-making [55] have also been observed in AD, but may not be a defining deficit of the disease. More recent research using the LARS showed that people with AD showed less apathy in the "emotional" dimension and the "self-awareness" dimension when compared to people with behavioral variant frontotemporal dementia [56] and supports our findings of Emotional apathy as not a hallmark of AD. While the Dimensional Apathy framework attempts to incorporate observable behavioral and neuropsychological deficits, similar to Levy and Dubois [27,28], how apathy subtypes map on to cognitive functioning is yet to be determined.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, deficits of emotional processing, social awareness [54] and emotional decision-making [55] have also been observed in AD, but may not be a defining deficit of the disease. More recent research using the LARS showed that people with AD showed less apathy in the "emotional" dimension and the "self-awareness" dimension when compared to people with behavioral variant frontotemporal dementia [56] and supports our findings of Emotional apathy as not a hallmark of AD. While the Dimensional Apathy framework attempts to incorporate observable behavioral and neuropsychological deficits, similar to Levy and Dubois [27,28], how apathy subtypes map on to cognitive functioning is yet to be determined.…”
Section: Discussionsupporting
confidence: 90%
“…Another FDG-PET study analysing a subsample of the ADNI dataset ( N = 95 AD; 203 MCI and 104 controls) reported a cross-sectional and longitudinal association between posterior cingulate hypometabolism and higher apathy scores. There was no relation between apathy and hypometabolism in the inferior temporal lobe or ACC [ 33 ], as was reported in the previously mentioned studies [ 30 , 32• ]. This finding must be interpreted with caution, because the researchers did not differentiate between healthy controls, MCI, or mild AD in their analysis.…”
Section: Neuroimaging Studiesmentioning
confidence: 72%
“…One recent investigation used positron emission tomography with 18F fluorodeoxyglucose (FDG-PET) to examine how brain metabolism is associated with apathy in AD cases [ 32 • ]. The researchers reported a relationship between apathy and right ACC hypometabolism in AD.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…6. The functional role of the involved regions suggests an association with a frequently observed clinical presentation of AD and SD characterized by apathy and agitation, associated with the right orbitofrontal cortex [72,73], and impairments in social behavior related to the right anterior temporal lobe [74]. According to Olson et al [75], social knowledge is part of semantic memory and involves memory about people including biographical information.…”
Section: Discussionmentioning
confidence: 99%